Fitness Level Of High School Students Based On Smoking Habits, Nutrient Intake, Physical Activity And Nutritional Status - Trina Astuti; Febriansyah Febriansyah (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
This study discusses the fitness level of male students based on smoking habits , nutrient intake , physical activity and nutritional status as measured by cardiorespiratory endurance using YMCA-3 minutes step test.The design is descriptive analytic with cross-sectional study. The data were collected from 67 male students at SMAN 108 Jakarta. Study results showed that 58,2 % student is not fit, 41,8 % student is light smoker, 89,6 % deficiency energy intake, 80,6 % deficiency protein intake, 71,6 % deficiency vitamin B1, 56,7 % deficiency vitamin C, 52,2 % deficiency Fe intake, 73,1 % having weight physical activity and 28,4% malnutrition status. Chi-Square Test shows that fitness level of students depends on smoking habits (p=0,039), energy intake (p=0,001), vitamin B1 intake (p=0,012), and Fe intake (p=0,039). In order to increase the fitness status , it is advisable for students to organize a healthy lifestyle by quitting smoking , exercising regularly and increasing daily nutrient intake